From a helix to a small cycle: metadynamics-inspired alpha v beta 6 integrin selective ligands - Di Leva, Francesco Saverio; Tomassi, Stefano; Di Maro, Salvatore; Reichart, Florian; Notni, Johannes; Dangi, Abha; Marelli, Udaya Kiran; Brancaccio, Diego; Merlino, Francesco; Wester, Hans-Juergen; Novellino, Ettore; Kessler, Horst; et al. (Angewandte Chemie-International Edition, 2018)
The RGD-recognizing alpha v beta 6 integrin has only recently emerged as a major target for cancer diagnosis and therapy. Thus, the development of selective, low-molecular-weight ligands of this receptor is still in great demand. Here, a metadynamics-driven design strategy allowed us to successfully convert a helical nonapeptide into a cyclic pentapeptide (6) showing remarkable potency and alpha v beta 6 specificity. NMR and docking studies elucidated the reasons for the high affinity and selectivity of this compound, setting the ground for the rational design of new alpha v beta 6-specific small peptides or even peptidomimetics. In vivo PET imaging studies demonstrated the potential use of 6 for medical applications.

Selective targeting of integrin alpha v beta 8 by a highly active cyclic peptide - Reichart, Florian; Maltsev, Oleg V.; Kapp, Tobias G.; Raeder, Andreas F. B.; Weinmueller, Michael; Marelli, Udaya Kiran; Notni, Johannes; Wurzer, Alexander; Beck, Roswitha; Wester, Hans Juergen; Steiger, Katja; Di Maro, Salvatore; et al. (Journal of Medicinal Chemistry, 2019)
Integrins play important roles in physiological and pathophysiological processes. Among the RGD-recognizing integrin subtypes, the alpha v beta 8 receptor is emerging as an attractive target because of its involvement in various illnesses, such as autoimmune diseases, viral infections, and cancer. However, its functions have, so far, not been investigated in living subjects mainly because of the lack of a selective alpha v beta 8 ligand. Here, we report the design and potential medical applications of a cyclic octapeptide as the first highly selective small-molecule ligand for alpha v beta 8. Remarkably, this compound displays low nanomolar alpha v beta 8 binding affinity and a strong discriminating power of at least 2 orders of magnitude versus other RGD-recognizing integrins. Peptide functionalization with fluorescent or radioactive labels enables the selective imaging of alpha v beta 8-positive cells and tissues. This new probe will pave the way for detailed characterization of the distinct (patho)physiological role of this relatively unexplored integrin, providing a basis to fully exploit the potential of alpha v beta 8 as a target for molecular diagnostics and personalized therapy regimens.